Physician versus the smoking habit of the patient - Dulger, Seyhan; Budak, Ersin; Sengoren Dikis, Ozlem; Yildiz, Tekin (The European Research Journal, 2017)
Objective. This study has aimed to investigate the bases, conditions and the characteristics of the counselling approach of physicians serving in diverse branches of medicine in our hospital.Methods. Volunteering physicians working in our hospital were given a questionnaire designed to investigate their approach in counselling against cigarette smoking habits of patients arriving at the emergency services, the polyclinics and the specialized clinics. The relationships between the answers given to the questions asked and the professional branches or the characteristics of the approach to counselling was analysed statistically.Results. The study enrolled 64 volunteering physicians. There were statistically significant differences in the approaches of the physicians working at the emergency services, polyclinics and the clinics (p